Islamic Methodology Concerning Student-Teacher Relationships for Sustainable Development: The Qur’anic Musa-Khidr Experience - Adebayo, Rafiu Ibrahim (The Journal of Rotterdam Islamic and Social Sciences, 2016)
This article examines student-teacher relationships from the perspective of Islam. Historical, descriptive, and interpretative methods were adopted. Qur’anic passages relevant to the acquisition of knowledge were used as the theological framework. The article highlights the relevance of student-teacher relationships for education, the necessity for constantly updating knowledge to meet the demands of time, the etiquette of teaching and learning as well as healthy student-teacher relationships and their implications for sustainable development. It therefore recommends the integration of Islamic education theories into the existing theories taught to students in the educational institutions for the attainment of sustainable development in Africa.